1999
DOI: 10.1177/026988119901300310
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of serotonergic agonists withvarying efficacy at the 5-HT1A receptor on core body temperature: modification by the selective 5-HT1A receptor antagonist WAY 100635

Abstract: A reduction in core body temperature is one of the characteristic consequences of 5-HT1A receptor activation in rodents. In this study, we characterized the hypothermic effects of four 5-HT1A receptor ligands with varying affinity and selectivity at the 5-HT1A receptor. 8-OH-DPAT and flesinoxan (full agonists); ipsapirone (selective partial agonist) and eltoprazine (non selective partial agonist), all induced a dose-dependent reduction in core body temperature, which was maximal 30 min subsequent to administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…Flesinoxan-induced hypothermia tends to confirm results from several animal and human studies assessing the effect of different 5-HT 1A receptor agonists on core body temperature (Anderson et al 1990;Lesch et al 1990;Millan et al 1993;Young et al 1993;Kahn et al 1994;Cleare et al 1998;Cryan et al 1999, McAllisterWilliams et al 2001). More specificaly, our results are in agreement with those of Seletti et al (1995), who reported a dose-related decrease in body temperature after administration of flesinoxan (7 and 14 g/kg).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Flesinoxan-induced hypothermia tends to confirm results from several animal and human studies assessing the effect of different 5-HT 1A receptor agonists on core body temperature (Anderson et al 1990;Lesch et al 1990;Millan et al 1993;Young et al 1993;Kahn et al 1994;Cleare et al 1998;Cryan et al 1999, McAllisterWilliams et al 2001). More specificaly, our results are in agreement with those of Seletti et al (1995), who reported a dose-related decrease in body temperature after administration of flesinoxan (7 and 14 g/kg).…”
Section: Discussionsupporting
confidence: 59%
“…This hypothermic effect is probably mediated through the stimulation of 5-HT 1A receptors. Indeed, recently, Cryan et al (1999) demonstrated that pretreatment with the selective 5-HT 1A receptor antagonist WAY 100635 blocked hypothermic response to flesinoxan in rats. Moreover, flesinoxaninduced hypothermia could be due at least in part to the stimulation of somatodendritic 5-HT 1A receptors (Cowen 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Ipsapirone induces cortisol secretion via release of ACTH rather than by direct action on the adrenal gland (Przegalinski et al 1989). The assumption that ipsapirone's hypothermic effect and the stimulation of ACTH and cortisol primarily reflect 5-HT 1A receptor function is also supported by the observation that these responses can be antagonized by 5-HT 1A receptor antagonists (Goodwin et al 1987;Hamon et al 1987) and by recent findings confirming the utility of hypothermia as a robust in-vivo probe of 5-HT-1A receptor function (Cryan et al 1999;Oerther and Ahlenius 2001). However, further studies are necessary to clarify whether cortisol and temperature responses are mediated by different mechanisms (Cowen 2001).…”
mentioning
confidence: 89%